Indonesia's Defense Diplomacy in Lebanon through The Peacekeeping Force of the United Nations Interim Force in Lebanon (UNIFIL) - Sugiyanto; Riduan, Muhammad; Hermawan, Yoghi; Torang Avery Louerens, Jafirman; Primawanti, Henike (Future Science, 2024)
This paper offers an overview of Indonesia's military diplomacy through peacekeepers serving as members of the United Nations Interim Force in Lebanon (UNIFIL). In researching Indonesian defense diplomacy, the researcher used Chyre's theoretical framework of defense diplomacy, which focuses on peacekeeping missions. The method in this research is qualitative to explain, describe, and describe various tools and resources that can be used in collecting and analyzing data in the form of spoken or written language. Data collection techniques in this research use interviews, documentation studies, archival studies, and internet-based studies which are then managed and analyzed to conclude. This research found that Indonesian defense diplomacy through the UNIFIL peacekeeping force played a role in preventing armed conflict carried out by the Israel Defense Force (IDF) with the Lebanon Armed Force (LAF) on the border of the two countries by conducting routine patrols. Indonesian peacekeeping forces also established relations with the Lebanese community by organizing free medical treatment activities for the Lebanese community, holding social activities, and introducing Indonesian culture.